அவளுக்கு வெயில் என்று பெயர் கவிதைத் தொகுப்பில் பெண் கருத்தாக்கங்கள்/ Feminist Ideology in the Poetic Anthology Avalukku Veyil Endru Peyar - ஜெ. அரவிந்தன்/J. Aravindan; முனைவர் நா.சிவாஜிகபிலன்/Dr. N. Sivajikapilan (Chenkaantal)
Tamilachi Thangapandian is a Tamil Poetess. She makes the readers feel young by immersing the memorable words in her poems. She weaved a little in love and a little in the sun and makes love to the sun in her poetry. It evinces a bubbling loving-kindness that awakens the inner self. She makes the scorching sun delicious and similes through her poetry. The poet's love poems protect the world from moisture and dryness. In the literary arena, when a man writes love poems, male dominance will be there. In the love poems written by women, one cannot see a single word that expresses their dominance. On the contrary, it is not an exaggeration to say that this also breaks the tradition that women have been following. Andal boldly elicited her thoughts in her hymns for the sake of God. Similarly, the poet Tamilachi Thangapandian has created love poems that are as beautiful as a railway track without getting stuck in cultural traditions.